Frequency of Lower Urinary Tract Symptoms Among Normal-Weight, Overweight, and Obese Pakistani Male - Ahmed, Shabir; Syed Khurram Sharif (Medical Journal of South Punjab, 2024)
Objective: To investigate the lower urinary tract symptoms and their effect on the quality of life of obese and non-obese Pakistani population. Methods: This was a cross-sectional study that was conducted at urology department of Peoples University of Medical & Health Sciences Nawabshah from January 2024 to December 2024. Data on the quality of life of patients with lower urinary tract symptoms (LUTS) were collected from the study population using a questionnaire administered in a hospital setting. The study utilized the King’s Health Questionnaire, which comprises eight sections: general health perceptions, impact on life, role limitations, physical and social limitations, personal relationships, emotions, sleep and energy, and incontinence severity measures. Results: In this study, data were collected from 190 participants with a mean age of 30 ± 55.0 years. Among the participants, 32.5% were normal weight, 31% overweight, and 35.5% were obese. The prevalence of urinary symptoms, including hesitancy, incomplete emptying, urgency, nocturia, urge incontinence, stress incontinence, nocturnal enuresis, intercourse incontinence, and bladder pain, as well as the number of urinations per 24 hours and per night, was significantly higher among obese participants. Conclusion: Higher prevalence of LUTS among obese patients compared to nonobese patients was observed. Obese patients reported significantly higher deterioration of the quality of life as a result of LUTS compared to nonobese patients.